Der Wandel in der Geldpolitik – Anpassung der geldpolitischen Instrumente an die aktuellen Herausforderungen - Meklenburg, Bettina (Estonian Discussions on Economic Policy, 2018)
The present article deals with different instruments of monetary policy of the European Central Bank and the Bundesbank. After a period of time the adaption of the instruments is necessary for the effectiveness and assertive force of the monetary policy. At first, the requirement of central bank money is necessary, both to hold the minimum reserve and autonomous factors, including the delivery of cash to bank customers. In order to meet their reserve requirements the institutions have to hold balances, which they regularly get by participate in open market operations. I will present the development of the conventional instruments to the non-conventional instruments, which were introduced in 2008 after the financial crises